Evaluasi sistem informasi kesehatan di Puskesmas Kabupaten Konawe: A literartur review - Yunita, Dewi; Amalia, Risqi; Ismayanti, Ismayanti; Darmawati, Darmawati; Risnawati, Risnawati; Risky, Sartini (Holistik Jurnal Kesehatan, 2026)
Background: The implementation of health information systems in community health centers aims to improve the efficiency of healthcare services. however, limited trained human resources, inadequate infrastructure, and suboptimal data management remain major obstacles to implementation. Purpose: To analyze the challenges faced in health information systems implementation in community health centers. Method: This literature review used a systematic approach and narrative synthesis. A literature search was conducted through electronic databases such as Google Scholar, Garuda, PubMed, and ScienceDirect, focusing on articles published between 2021 and 2025. Relevant articles were selected based on predetermined inclusion and exclusion criteria. Results: The literature review indicates that although health information systems implementation can improve healthcare efficiency, many community health centers still face significant obstacles, including a shortage of trained personnel, infrastructure issues, and the system's inability to support comprehensive health management. Limitations in data management, duplicate input, and lack of integration between applications are key challenges in health information systems implementation in community health centers. The implementation of the health information system in community health centers shows significant potential to improve the efficiency of healthcare services, but remains hampered by various issues related to human resources, infrastructure, and systems that are not yet integrated. Conclusion: The implementation of the health information system in various community health centers in Indonesia and other countries shows significant potential to improve the efficiency of healthcare services, although it still faces various challenges. The main obstacles identified include limited trained personnel, lack of adequate training, inadequate infrastructure, and problems with data management and connectivity. Despite various efforts, such as training and system development, these obstacles still hinder the optimal implementation of the information system.   Keywords: Community Health Center; Evaluation; Health Information System.   Pendahuluan: Implementasi Sistem Informasi Kesehatan (SIK) di puskesmas bertujuan untuk meningkatkan efisiensi pelayanan kesehatan. Namun, keterbatasan sumber daya manusia terlatih, infrastruktur yang tidak memadai, serta pengelolaan data yang kurang optimal masih menjadi kendala utama dalam penerapan sistem ini. Tujuan: Untuk menganalisis tantangan yang dihadapi dalam implementasi SIK di puskesmas. Metode: Penelitian literatur review dengan pendekatan sistematis dan sintesis naratif. Pencarian literatur dilakukan melalui basis data elektronik, seperti Google Scholar, Garuda, PubMed, dan ScienceDirect, dengan fokus pada artikel yang diterbitkan antara tahun 2021 hingga 2025. Artikel yang relevan dipilih berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan. Hasil: Literatur review menunjukkan bahwa meskipun implementasi SIK dapat meningkatkan efisiensi pelayanan kesehatan, banyak puskesmas yang masih menghadapi kendala signifikan, termasuk kekurangan tenaga kerja terlatih, masalah infrastruktur, serta ketidakmampuan sistem dalam mendukung manajemen kesehatan yang komprehensif. Keterbatasan dalam pengelolaan data, penginputan ganda, serta kurangnya integrasi antar aplikasi menjadi tantangan utama dalam pengoperasian SIK di puskesmas. Penerapan SIK di puskesmas menunjukkan potensi besar dalam meningkatkan efisiensi pelayanan kesehatan, namun masih terhalang oleh berbagai masalah terkait sumber daya manusia, infrastruktur, dan sistem yang belum terintegrasi. Simpulan: Penerapan Sistem Informasi Kesehatan (SIK) di berbagai puskesmas di Indonesia dan negara lain menunjukkan potensi besar dalam meningkatkan efisiensi pelayanan kesehatan, meskipun masih menghadapi berbagai tantangan. Kendala utama yang ditemukan meliputi keterbatasan tenaga kerja yang terlatih, kurangnya pelatihan yang memadai, infrastruktur yang tidak memadai, serta masalah dalam pengelolaan data dan konektivitas. Meskipun berbagai upaya telah dilakukan, seperti pelatihan dan pengembangan sistem, hambatan-hambatan tersebut masih menghalangi implementasi sistem informasi yang optimal.   Kata Kunci: Evaluasi; Puskesmas; Sistem Informasi Kesehatan.